Simplify: (xp/xq)p+q . (xq/xr)q+r . (xr/xp)r+p

(xp/xq)p+q *

(xq/xr)q+r *

(xr/xp)r+p

=(xp-q)p+q *

(xq-r)q+r *

(xr-p)r+p

=(x)p2-q2 *

(x)q2-r2 *

(x)r2-p2

=(x)p2-q2+q2-r2+r2-p2

=(x)0

=1

  • 17

Please answer someone, My exams are near and I don't have tutions!

  • -1

Thanks alot friend!

  • 1

nakush i clicked continuosly and you got three thumbs up

  • 2

(xp/xq)p+q*

(xq/xr)q+r*

(xr/xp)r+p

=(xp-q)p+q*

(xq-r)q+r*

(xr-p)r+p

=(x)p2-q2*

(x)q2-r2*

(x)r2-p2

=(x)p2-q2+q2-r2+r2-p2

=(x)0

=1

hope it helps

  • 2
What are you looking for?